Al-Rahn from an Islamic jurisprudential perspective - Awang, Abdul Bari; Md Harun, Ahmad Syahir; Awang Hamat, Mohd Afandi; Sitiris, Miszairi (Alhikmah Research & Publication Centre, 2025)
Rahn is a transaction that helps people when they are in need of money. A pledgor will pledge his property for getting fast money from the pledgee and a certain safekeeping fee will be charged as a service to the pledgor. Islam has allowed rahn because it helps people who are in financial difficulties. By the necessity of this transaction, the poor customers will benefit and make rahn as a solution to their problems. This article aims to offer a juristic exposition of the pillars and conditions to perform rahn based on the Scholars’ views. The result shows that Ha¬nafīs, Mālikīs, Shāfiʿis and Hanbalīs allow the transaction of rahn with certain conditions.